Robust bimetallic Pt–Ru catalysts for the rapid hydrogenation of toluene and tetralin at ambient temperature and pressure - Stanley, Jessica N.G.; Heinroth, Falk; Weber, Cameron C.; Masters, Anthony F.; Maschmeyer, Thomas (Applied catalysis. A, General, 2013)
[Display omitted] ► Alloy nanoparticles of Pt–Ru were synthesised. ► The complete catalyst synthesis was performed in air. ► Toluene was hydrogenated under ambient conditions and with no special precautions. ► The alloy with a molar ratio of 1 Pt to 1.5 Ru was much more active than either of the metals by themselves. ► The synergistic alloy may hold the key to a simple reversible hydrogen storage system, operating under mild conditions. To facilitate the drive towards ever lower energy, ‘greener’ processing, robust bimetallic aluminosilicate-supported Pt–Ru catalysts that can operate under atmospheric conditions have been developed for the rapid room temperature hydrogenation of aromatics (toluene and tetralin) at 1atm H2. The toluene/methylcyclohexane couple has the added interest of being a promising cyclic hydrocarbon combination for the storage of hydrogen. The easily handled air-stable catalysts were prepared using the incipient wetness method and characterised by ICP-AES, XRD, TEM as well as nitrogen sorption measurements. Compared to their monometallic counterparts, the bimetallic catalysts displayed significantly higher turn-over-frequencies (TOFs), consistent with a synergistic relationship between platinum and ruthenium.